Adjusting properties of electrode pitch with fractions of coal tar - Starovoit , A.G.; Malyi , E.I.; Sorokin , E.L.; Starovoit , M.A.; Popova , O.Yu. (Theory and Practice of Metallurgy, 2025)
The paper presents the investigation results of the organic mass modification of the impregnating pitch of coal tar with low pyrolysis degree. The processes that form the pitch operational properties in the impregnation technology of graphitized electrodes were studied. Specific features of the modifying additive effect on the quality characteristics of the pitch and its group composition were established. Such technological approach makes it possible to intensify the impregnation process of blanks for graphitized electrodes.